2020
DOI: 10.1038/s41379-020-0575-3
|View full text |Cite|
|
Sign up to set email alerts
|

Frequent traces of EBV infection in Hodgkin and non-Hodgkin lymphomas classified as EBV-negative by routine methods: expanding the landscape of EBV-related lymphomas

Abstract: The Epstein–Barr virus (EBV) is linked to various B-cell lymphomas, including Burkitt lymphoma (BL), classical Hodgkin lymphoma (cHL) and diffuse large B-cell lymphoma (DLBCL) at frequencies ranging, by routine techniques, from 5 to 10% of cases in DLBCL to >95% in endemic BL. Using higher-sensitivity methods, we recently detected EBV traces in a few EBV-negative BL cases, possibly suggesting a “hit-and-run” mechanism. Here, we used routine and higher-sensitivity methods (qPCR and ddPCR for conserved EBV ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…Moreover, a role in the pathogenesis was also attributed to EBV+ bystander cells, given that EBV + DLBCL patients and EBV − DLBCL patients with EBV+ bystander cells tended to have high and high-intermediate International Prognostic Index scores and poorer prognosis than EBV − DLBCL patients without EBV+ bystander cells [ 40 ]. In addition, traces of EBV infection were detectable by high-sensitivity methods in several EBV-associated lymphomas such as DLBCL, suggesting a “hit-and-run” mechanism [ 47 ]. Therefore, EBV may be involved in the pathogenesis of lymphoma more widely than recognized so far.…”
Section: Epidemiology Of Ebv + Dlbcl In Different Populationsmentioning
confidence: 99%
“…Moreover, a role in the pathogenesis was also attributed to EBV+ bystander cells, given that EBV + DLBCL patients and EBV − DLBCL patients with EBV+ bystander cells tended to have high and high-intermediate International Prognostic Index scores and poorer prognosis than EBV − DLBCL patients without EBV+ bystander cells [ 40 ]. In addition, traces of EBV infection were detectable by high-sensitivity methods in several EBV-associated lymphomas such as DLBCL, suggesting a “hit-and-run” mechanism [ 47 ]. Therefore, EBV may be involved in the pathogenesis of lymphoma more widely than recognized so far.…”
Section: Epidemiology Of Ebv + Dlbcl In Different Populationsmentioning
confidence: 99%
“…Unfortunately, no information on EBV serology was available for comparative analysis. Additionally, our results need to be interpreted in the context of recent observations by Mundo et al who recently reported on a significant proportion of B-cell lymphomas which were false negative for EBV by routine techniques [ 40 ].…”
Section: Discussionmentioning
confidence: 66%
“…The standard method for assaying for EBV in tumors is through the detection of the EBERs. However, analyses of biopsies have found multiple cases of BL that were EBER-negative and harbored partial viral miRNAs and some genomes ( Mundo et al., 2017 ; Mundo et al., 2020 ). This hypothesis and the findings consistent with it could indicate that the contribution of EBV to the pathogenesis of BL is greater than previously thought.…”
Section: Discussionmentioning
confidence: 99%